Ghostly Objects and the Horrors of Ghastly Ancestors in the Ghost Stories of Louisa Baldwin. Issue 2 (3rd April 2022) - Heholt, Ruth; Lloyd, Rebecca
ABSTRACT: This article examines the late Victorian ghost stories of Louisa Baldwin. Looking at several stories from her 1895 collection The Shadow on the Blind, we argue that, although her work is a part of the ongoing tradition of women's ghost stories in the nineteenth century, they differ from most by the weight of emphasis given to family, ancestry, and the importance of material, inherited objects. We argue that Louisa cannot be separated out from her family, who included sisters married to Edward Poynter, and Edward Burne-Jones; her nephew Rudyard Kipling, and her son Prime Minister (to be) Stanley Baldwin. There is a material weight of family evident in her work that haunts her characters through ancestry and heritage. The ghost stories discussed here display a sense of fatality; of destiny, of inescapability, and finally of a dwindling and the dying out of the ancestral line. Tracing some sort of autobiographical criticism of over-bearing families, this article explores both real, and spectral "ghastly ancestors".